Senior High School Students’ Perceptions of Using Video Projects to Develop Speaking Skills - Anjeli Rahmadani; Syarifuddin Dollah; Amra Ariyani (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study investigates senior high school students' perspectives on using video projects to enhance their speaking skills. Although the increasing use of video projects in English language instruction is well documented, little is known about how students perceive this approach in actual classroom environments. Although students' real experiences may differ, some argue that video projects could increase confidence, motivation, and opportunities for speaking practice. The study was conducted to close the gap between theory and classroom practice and to present more convincing evidence. A quantitative descriptive strategy was employed in this study. Students from two senior high schools MAS Mannilingi Bulo-Bulo and MAN, Jeneponto participated. To ensure equal participation across classes, random cluster sampling was used to choose the sample. Data was collected using a questionnaire. Students' interest, motivation, confidence, challenges, and overall sentiments regarding the use of video projects in speaking exercises were assessed in the questionnaire. The findings indicate that most students at both institutions held favorable views of learning through video projects. According to many students, making films improves speaking practice and allows them to express their thoughts more freely. Additionally, they reported that rehearsing several times before recording the final version reduced their nervousness. Because this approach provides more time to practice and rehearse their speaking performance, students report that it enhances their confidence, fluency, and pronunciation. Although a few students reported issues such as limited phone storage or difficulty editing films, these didn't substantially detract from their generally favorable opinion. In conclusion, video projects are perceived by students from MAN Jeneponto and MAS Mannilingi Bulo-Bulo as beneficial and inspiring activities that enhance their speaking skills.